The Relationship between Sensory Marketing and Customer Satisfaction and Loyalty in Luxury Sports Clubs - Zahra Rabbani Nik; Ali Benesbordi; Parvin Shoshi Nasab; Javad Fesanghari (Sports Business Journal, 2021)
Purpose: This study aimed to investigate the relationship between sensory marketing and customer satisfaction and loyalty of luxury sports clubs.Methodology: The study's statistical population includes all customers of luxury sports complexes and clubs in Mashhad. Using stratified random sampling method and with the help of G-Power software, which is a software for determining the number of samples, 149 people were selected as a statistical sample. The questionnaire with three sections of sensory marketing, loyalty, and satisfaction was used to collect information. This questionnaire contained 13 questions in the sensory marketing section, four questions in the loyalty section, and four questions in the satisfaction section. Each was set as a range of 5 Likert options. Ten professors of sports management confirmed the validity of the questionnaire. Cronbach's alpha also confirmed the reliability of the tool. Spearman test and structural equation modelling in PLS software were used to analyze the data. The results showed a positive and significant relationship between the dimensions of sensory marketing with satisfaction and loyalty. There is also a positive and meaningful relationship between satisfaction and loyalty. Sensory marketing consisting of sensory, emotional, behavioral, mental, and social experiences plays an essential role in customer satisfaction.Findings: The results show that sensory marketing promotes loyalty among athletes in luxury sports clubs by creating satisfaction.Originality: Factors such as the appearance of the product should be considered because aesthetic features affect both emotions and perceptions of quality. sensory marketing, consisting of sensory, emotional, behavioral, mental, and social experiences, has an important role in customer satisfaction.